10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Perceived infectability is the self-assessed likelihood of illness, and its relations with physical and mental health play a pivotal role in many models and theories; however, no quantitative review has summarized these relations, which poses significant barriers to the progression of empirical research, and theoretical development. Variability in these relations may cause authors to habitually draw from atypical results, and study-level influences on these relations may remain undiscovered. The current article resolves these tensions by reporting a meta-analysis of 103 sources. We demonstrate that perceived infectability produces negative, moderate, and statistically significant relations with both physical health and mental health. Our results also support some study-level influences while failing to support others, indicating that our findings provide clear avenues for pursuing fruitful research while avoiding those with less potential. Our discussion advances theory by integrating these results, and we guide researchers toward crafting more specific hypotheses regarding these relations.